Improved crystallinity of the asymmetrical diketopyrrolopyrrole derivatives by the adamantane substitution. (April 2020) - Cigánek, Martin; Heinrichová, Patricie; Kovalenko, Alexander; Kučerík, Jiří; Vala, Martin; Weiter, Martin; Krajčovič, Jozef
Abstract: Alkylation of diketopyrrolopyrroles (DPPs) is a powerful tool for increasing the solubility and processability of these pigments. Moreover, alkylation contributes to solid state packing and structural ordering of DPPs. In this study, the influence of the alkylation and solubilization side group engineering to DPPs on the thermal and optical properties was systematically investigated. Two series (each containing 3 derivatives: N, N' -, N, O ′- and O, O ′-substituted examples) of alkylated DPPs by 2-ethylhexyl and ethyladamantyl substituents were synthesized. Separation of all formed DPP derivatives was accomplished in order to perform an in-depth study of their physicochemical properties. DSC measurements revealed that the O -substitution caused a decrease in the thermal stability of DPP derivatives. On the contrary, an ethyladamantyl side chain, as a rigid alicyclic substituent, contributed very effectively to the increase of the melting point and thermal stability. The new results provide insights into the development of DPP-alkylated regioisomers and their thermal and optical properties. Graphical abstract: Image 1 Highlights: Two series of asymmetrically substituted DPP derivatives were synthesized. Optical and thermal properties were comprehensively studied for all prepared DPP derivatives. The effects of the alkyl chain character and binding position in the DPP molecule were investigated. O -substitution caused a significant decrease in the thermal stability of DPP derivatives compared to N -alkylated. Ethyladamantyl side chain contributed very effectively to the increase of melting point and thermal stability.